International Legal Mechanisms for Holding the Russian Federation Accountable for Causing Environmental Damage as a Result of Armed Aggression against Ukraine - Liudmyla Golovko (Bratislava Law Review, 2023)
As a result of the armed aggression of the Russian Federation against Ukraine, significant damage was caused to the environment. Official data published by the Ministry of Ecology and Natural Resources of Ukraine regarding the extent of environmental damage already caused indicates catastrophic consequences. That is why it is important to establish the illegality of causing environmental damage as a result of hostilities, to properly collect evidence, establish the amount of damage caused and to hold the Russian Federation accountable for causing this damage. The steps taken by Ukraine to achieve the abovementioned tasks were disclosed. The article analyses existing international mechanisms for environmental protection during armed conflicts and the possibility of holding Russian Federation responsible for environmental damage caused to Ukraine as a result of armed aggression. A conclusion was made about the possibility of holding the Russian Federation accountable for environmental damage according to the customary norms of the law of international responsibility by creating a special international tribunal.